The Practice of Wearing Hijab in a Multicultural Mosque of America - Muhammad Sigit Andhi Rahman; Aini Firdaus (Humaniora, 2018)
This research examined the practice of wearing the hijab among Hampton Roads Muslim women of Islamic Center of Tidewater (known as the ODU Mosque) in Norfolk, Virginia. This research asked two main questions: how did Muslim women at the ODU Mosque negotiate the social meanings embedded in the hijab? And, how did the ODU mosque as a cultural institution and as a multicultural space for Muslim women shape their practice of wearing the hijab? This research followed qualitative research method. The observation was primarily conducted during November 2017. For this research, interviews were conducted with five Muslim women who were at least 18 years of age, resided in Norfolk. This research finds that there is a cultural hybridization of the practices of wearing the hijab among Muslim women of this community. Moreover, by using the concept of ‘space’ by de Certeau, the researchers contend that the mosque has become not only a place of worship but space for them to interact and negotiate their Islamic practices or so-called their Muslimness. The ODU mosque is a space for them to negotiate their practices of Islamic rulings including the hijab.